Crusted Scabies in an Immunocompetent Child : A Case Report - Budiyarto, Larasati; Mumtazah, Devi Arofah (Journal of Pakistan Association of Dermatologists, 2023)
Abstract Introduction: Crusted scabies is an uncommon and debilitating type of scabies that is distinguished by hyperinfestation of millions mites and the clinical hallmark of hyperkeratotic skin crust. Case Report: This is a case report of crusted scabies in a 10-year-old immunocompetent female child. The case was first misdiagnosed at previous healthcare center as ichthyosis vulgaris and was given prolonged topical corticosteroid with no improvement. Microscopic examination of skin scrapings revealed multiple Sarcoptes scabiei and their eggs. Diagnosis of crusted scabies was made. Patient’s clinical outcomes improved after receiving combination therapy of oral ivermectin, topical permethrin 5% and topical keratolytic agents. Conclusion: Misdiagnosis of crusted scabies may pose risk of uncontrolled infestation and perpetuate an outbreak in society. It is also associated with complication of secondary bacterial infection. Therefore, it is important for clinicians to acknowledge the diagnosis and management of crusted scabies to improve clinical outcomes and control disease transmission.